Irrigation Performance Assessment in Krishna Western Delta Using Remote Sensing and GIS - M, L.M. Nagendra Kumar; Rao, D.Sai Gangadhara; Venu, P; Kumar, H.V Hema; Prasad, P.R.K (Journal of Agricultural Engineering, 2011)
Satellite provides a convenient platform to observe earth features, capable of giving spatial data, which is continuous in nature. Satellite imageries at regular intervals are useful in generating information on the status of irrigation commands at different time intervals for performance evaluation. The present study was carried out in Krishna Western Delta (KWD), with the data of IRS P6 (Resource Sat-I) LISS III to evaluate the overall performance of irrigation during Kharif 2005 in Modukur command using performance indicators and comparing with historical values using Earth Resource Data Analysis System (ERDAS) 9.0 and Model Crop Irrigation Water Requirement (CRIWAR). Irrigation performance assessment was judged by arriving at different performance indicators like uniformity of water application index (2.11-3.26) indicating highly non-uniform water distribution and water productivity (4.3 kg.ha?Â¹.mm?Â¹). Maximum NDVI image derived from two different satellite imageries at different intervals were used to develop yield model. The relation between NDVI values and paddy yield was observed to be quadratic with R2 as 0.9886.